Dental safety of short-term doxycycline use in children under 8 years: a systematic review and meta-analysis - Rajan, Anusiga Sigamani; Gopal, Muthu; Periyathambi, Madhumidha; Kuttiatt, Vijesh Sreedhar (Frontiers in Pharmacology, 2025)
BackgroundDoxycycline is widely used to treat various bacterial infections and has significant global implications, especially as the preferred medication for scrub typhus and leptospirosis. However, its use is limited in children below 8 years of age due to potential adverse effects on teeth and bones. This study aims to assess the risk of dental adverse events associated with doxycycline, a tetracycline-class antibiotic, in children under 8 years of age.MethodsIn this review, we searched PubMed, the Cochrane Library, and Google Scholar for studies published until November 2023. We included studies administering doxycycline to children under 8 years, focusing on dose, duration, and dental adverse events to assess the safety of doxycycline.ResultA total of 325 articles were initially retrieved, of which 5 studies were available for analysis. This review included information on 162 children who were treated with doxycycline between the ages of 0 and 8 years. The median age at doxycycline administration was 4.25 years and interquartile range (IQR) of 2.065–5.563 years. The oral dosage, based on weight, had a median of 2.3 mg/kg/day, with an IQR of 1.525–5.438 mg/kg/day. The median duration of drug administration was 8.5 days and the IQR of 6–12.5 days. We found a pooled proportion of adverse events of 0.21 (95% CI: 0.13–0.28).ConclusionThis review suggests that the occurrence of teeth-related adverse events with short-term doxycycline use is minimal, with a low incidence reported. While these findings offer a preliminary basis for the use of doxycycline in children under 8 years of age, the limited number of studies underscore the need for further research to evaluate its therapeutic use and implication for paediatric guidelines.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/myprospero, Identifier CRD42023494713.